Trends in the HIV related hospital admissions in the HAART era in Barbados, 2004–2006 - Kilaru Krishna R; Kumar Alok; Sandiford Shelly; Forde Sheila (AIDS Research and Therapy, 2007)
Abstract Background To investigate the reasons for hospitalizations and its outcome in the era of HAART in Barbados. This report also describes the profile of the HIV infected persons who are hospitalized in the HAART era. Methods This is a retrospective study of HIV related admissions in this country. We examined the admission case notes of all the adult admissions to the Queen Elizabeth Hospital where one of the discharge diagnosis was HIV infection during the April 2004 through March 2006. Data collected included patients' profile, including the date of diagnosis of HIV infection, outcome of the current admission in term of discharge or death and the final diagnosis at the time of discharge or death. Results Over the 24 months period there were 431 adult admissions to the medical wards of the Queen Elizabeth Hospital where one of the discharge diagnosis was HIV infection and this accounted for 5.9% of all medical admissions. 258(60%) admissions were in persons who were known to be HIV infected prior to the current admission, where as diagnosis of HIV infection was made for the first time during the current admission in case of remaining 76(47.5%) cases. Nearly half of those hospitalized, had a CD 4 cell counts of < 200/μL. Over all, opportunistic infection was the commonest (35%) discharge diagnosis, followed by serious bacterial infections, anemia and HIV nephropathy. The outcome of these admissions was death in 30 (14.2%) cases where as patient was discharged out in the remaining 181 (85.8%) cases. Of the medical admissions with HIV as one of the discharge diagnosis during the period April 04 through March 05, 43% were newly diagnosed HIV infection and the corresponding figure for the period April 05 through March 06 was 35% (P = 0.54). During the April 05 through March 04 significantly higher proportion of HIV infected adults had Anemia with a Hemoglobin less than 10 g/dL (P = 0.044), HIV related nephropathy (P = 0.0003), HAART toxicity (P = < 0.0001) and a Non-AIDS related conditions (P = 0.043) as one of the final discharge diagnosis. Conclusion A significant proportion of patients admitted with HIV infection were the newly diagnosed and severely immuno-supressed. An opportunistic infection continues to be the commonest discharge diagnosis, although there was a growing trend in the proportion of the discharge diagnosis being HAART toxicity and Non-AIDS related conditions. Over all hospitalization of HIV infected persons still carries a significant risk of mortality.